IMPROVING SPATIAL UNDERSTANDING USING BILINGUAL PHRASES DESCRIBING POSITION IN ELEMENTARY CLASSROOM ACTIVITIESNALISIS - Siregar, Tiarnita Maria Sarjani Br; Ginting, Sinthya Wardhani; Aulia, Rahma; Arwila, Arwila; Maharaja, Wina Yunita; Utami, Tri Setia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Spatial understanding is an important component in early cognitive development and plays a major role in mathematical reasoning, problem solving, and everyday navigation. This study aims to examine the contribution of bilingual spatial phrases such as di depan / in front of, di antara / between, di samping / next to, and di belakang / behind in improving the spatial understanding of elementary school students. The method used is a literature review by synthesizing journal articles and scientific books published in the last five to ten years that are relevant to spatial language, bilingual scaffolding, and classroom learning strategies. The synthesis results indicate that explicit exposure to spatial language strengthens children's mental representation of object positional relationships, while the use of bilingual phrases further enhances understanding through the process of mapping concepts from the first language to the target language. Interactive learning activities such as direction games, object arrangement, map tasks, and digital games can improve spatial vocabulary, reasoning skills, and student engagement in learning. In addition, the use of bilingual spatial language creates an inclusive learning environment, increases confidence, and encourages active participation, especially for students with limited English skills. Thus, the integration of bilingual spatial phrases is an effective pedagogical approach that supports the cognitive, linguistic, and academic development of elementary school students. This study recommends the systematic application of multimodal and bilingual learning strategies in early learning to optimize the development of spatial understanding. ABSTRAK Pemahaman spasial merupakan komponen penting dalam perkembangan kognitif awal dan berperan besar dalam kemampuan penalaran matematika, pemecahan masalah, serta navigasi sehari-hari. Penelitian ini bertujuan menganalisis kontribusi frasa spasial bilingual seperti di depan / in front of, di antara / between, di samping / next to, dan di belakang / behind dalam meningkatkan pemahaman spasial siswa sekolah dasar. Metode yang digunakan adalah tinjauan pustaka dengan mensintesis artikel jurnal dan buku ilmiah terbitan lima hingga sepuluh tahun terakhir yang relevan dengan bahasa spasial, scaffolding bilingual, dan strategi pembelajaran di kelas. Hasil sintesis menunjukkan bahwa paparan eksplisit terhadap bahasa spasial memperkuat representasi mental hubungan posisi objek pada anak, sementara penggunaan frasa bilingual semakin meningkatkan pemahaman melalui proses pemetaan konsep dari bahasa pertama ke bahasa sasaran. Aktivitas pembelajaran interaktif seperti permainan arah, penataan objek, tugas peta, dan permainan digital mampu meningkatkan kosakata spasial, kemampuan penalaran, serta keterlibatan belajar siswa. Selain itu, penggunaan bahasa spasial bilingual menciptakan lingkungan belajar yang inklusif, meningkatkan kepercayaan diri, dan mendorong partisipasi aktif terutama bagi siswa dengan kemampuan bahasa Inggris terbatas. Dengan demikian, integrasi frasa spasial bilingual merupakan pendekatan pedagogis efektif yang mendukung perkembangan kognitif, linguistik, dan akademik siswa sekolah dasar. Studi ini merekomendasikan penerapan strategi pembelajaran multimodal dan bilingual secara sistematis dalam pembelajaran awal untuk mengoptimalkan perkembangan pemahaman spasial.